Investigating factors influencing the probability of survival to metamorphosis of boreal toads at multiple scales - Crockett, John, author; Bailey, Larissa, advisor; Muths, Erin, committee member; Funk, Chris, committee member; Huyvaert, Kathryn, committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.